Augmented Innate and Adaptive Immune Responses Under Conditions of Diabetes–Filariasis Comorbidity - Sibi, Joy Manohar; Mohan, Viswanathan; Munisankar, Saravanan; Babu, Subash; Aravindhan, Vivekanandhan (Frontiers in Immunology, 2021)
Metainflammation, as seen in chronic diabetes subjects impairs immunity and increases the susceptibility to infections. In the present study, the effect of diabetes on immune response against filariasis was studied. Both toll-like receptor (TLR) mediated and crude antigen induced immune responses were quantified, in whole blood cultures from filariasis infected subjects (LF+), with and without diabetes. Blood cultures were stimulated with TLR ligands (TLR2 and TLR4) or filarial antigen or were left unstimulated (control) for 18 hrs. Cytokine, chemokine and defensin secretion was quantified by ELISA. Expression of HLA-DR, B7-1, B7-2, activation marker (CD69) and Th (Th1, Th2, Th17 and Th9) phenotypes were quantified by flow cytometry. Expression of immunomodulatory effectors (Cox-2, HO-1, IDO-1 and p47Phox) and Th polarizing transcription factors (T-bet, GATA3 and ROR-γt) were quantified by quantitative PCR. Secretion of IL-27, IL-1Ra, IL-12, IL-33, IL-9 and SDF-1, were increased under diabetes condition with increased Th9 polarization and increased expression of Cox-2 and IDO. Overall, diabetes was found to augment both TLR mediated and antigen-induced inflammation which can promote chronic pathology in LF+ subjects.